Peranan Perangkat Desa Dalam Membantu Pelaku UMKM Mengembangkan Usahanya - Nia Endri Wiranti; Lince Magriasti; Aldri Frinaldi (FKIP, Universitas Palangka Raya, 2024)
The role of the village in advancing the community's economy, such as MSME actors, is one of the functions of the government itself, therefore the role of the village government plays a very important role and must be increased. The spearhead of the community in receiving and feeling the influence of prosperity is the village government, both in terms of material assistance and others. So that the Government's level of success in building the nation makes villages the first benchmark. Apart from that, the function that village officials must be aware of is not just working in the administrative sector but must be able to become Facilitators and Regulators for MSME actors in finding the best solutions to improve their business.